Administration, prosopography and appointment policies in the Roman empire : proceedings of the First Workshop of the international network Impact of Empire (Roman Empire, 27 B.C.-A.D. 406), Leiden, June 28-July 1, 2000 ; edited by Lukas de Blois. - Blois, Lukas de. (Impact of Empire;, 2001)
The title of this volume is 'Administration, Prosopography and Appointment Policies in the Roman Empire'. The papers contained in this volume focus on all three of these themes, within the context of the impact of the Roman empire upon the regions it dominated. The papers contained in the first part of the volume concentrate on appointment policies, career structures and the impact of military presence and recuitment, esp. in border provinces, in the period of the Principate (27 B.C. - A.D. 284). In the second part of the volume the reader will find papers on Roman jurists, administrators, and bureaucrats and articles about administrative procedures, the administration of justice, rescripts and the influence of learned juridical treatises in various regions of the Roman empire. The last section of the volume presents contributions on the impact of the Roman imperial administration and appointment policies on communal rights and politics, the composition of local councils, local administrative structures, Romanisation, and social mobility of regional and local notables in various provinces of the Roman Empire.